Ease of Commercialization and Downstream Processing of Ginger-Processed Products - Ida Rosada; St. Sabahannur; Rasmeidah Rasyid Patingari; Nursyamsuryani Nursyamsuryani (Jurnal Manajemen Bisnis, 2022)
This research aims to analyze the input of raw materials and other inputs, receipts, and benefits, and analyze the added value of processed ginger products as herbal drinks. The processed ginger products analyzed are the syrup drink "Sarabba" and the spice syrup "Habbatussauda". The research was conducted on Ballaratea micro-businesses in Gowa Regency, South Sulawesi Province. Business analysis methods used include cost analysis, receipts, profits and R/C ratio. Value-added analysis using the Hayami method. The results of the value-added analysis showed that Sarabba syrup products gave an added value of Rp 349,382 / kg where every Rp 100 the value of sarabba syrup products gave an added value of Rp 70.58. The added value of spice syrup "Habbatussauda" amounted to Rp 548,116 / kg where every Rp100 value of spice syrup products "Habbatussauda" gave an added value of Rp 91.35.